Estado actual de la investigación científica publicada sobre los bosques de Colombia (2016)
The objective of this research was to review all scientific literature published on Colombian forests in order to learn more about knowledge gaps for a future research agenda. This study was focused on three topics 1) base line studies, 2) research on ecological dynamics and functioning of forests and 3) research with recommendations for forest management and conservation. We found 1627 published documents on Colombian forests including 1337 scientific articles, 60 book chapters, and 230 books. The most studied region was the Colombian Andes (699), with an important increase of publications during the last decade. Most of the documents are baseline studies, mainly on floristic composition. Studies on ecological dynamics and forest functioning (680) were more numerous than research on forest structure (370). 65% of the documents were open access, mainly scientific articles. In contrast, the majority of the books were not available in digital version. We found that less than 25% of the documents attempt to determine what is causing biodiversity loss. Additionally, only 102 (7.5%) of the documents provided explicit and feasible recommendations for forest management. We conclude that despite the great and growing amount of information published on Colombian forests there is still a gap between scientific research and the possibilities of implementation. This paper should become an important asset for a national research agenda that links scientific knowledge and planning exercises for a wise and integrative forest management in Colombia.